2020
DOI: 10.1186/s40663-020-0217-8
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and anthropogenic factors explain the variability of Fagus sylvatica treeline elevation in fifteen mountain groups across the Apennines

Abstract: Background: Fagus sylvatica forms the treeline across the Apennines mountain range, with an average elevation of 1589 m a.s.l. Previous studies evidenced that the current position of the treeline in the Apennines is heavily depressed as a result of a complex interaction between climatic factors and the past human pressure. In this study we correlated treeline elevation in the fifteen major mountain groups in the Apennines with selected climatic, geomorphological, and human disturbance variables in order to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
1
22
2
Order By: Relevance
“…European beech grew slowly at the highest elevation, in PE, where climatic and environmental conditions related to the altitude, limited plant growth (2127 m a.s.l.). As observed by Bonanomi et al (2020), the highest tree line, found in remote areas without evident anthropogenic disturbance, highlights the general depression of the tree line in central Apennines. Currently, in the Apennines, the average tree line occurs several hundred meters below the potential climatic limit of European beech.…”
Section: Discussionmentioning
confidence: 58%
“…European beech grew slowly at the highest elevation, in PE, where climatic and environmental conditions related to the altitude, limited plant growth (2127 m a.s.l.). As observed by Bonanomi et al (2020), the highest tree line, found in remote areas without evident anthropogenic disturbance, highlights the general depression of the tree line in central Apennines. Currently, in the Apennines, the average tree line occurs several hundred meters below the potential climatic limit of European beech.…”
Section: Discussionmentioning
confidence: 58%
“…towards its single-tree and group admixture in stands dominated by cold-resistant Norway spruce. When Norway spruce is not present, as in the Pyrenean, beech replaces silver fir (Hernández et al 2019) while fir replaces beech in the Apennine Mountains (Bonanomi et al 2020). Nevertheless, all three tree species can successfully coexist at elevations between ~ 600 and 1400 m a.s.l.…”
Section: Relevance Of the Results For Forest Management And Silviculturementioning
confidence: 99%
“…The mountainous veg-etation (over 1200 m a.s.l.) is dominated by Fagus sylvatica forests and, at the treeline, by scattered Pinus leucodermis (Bonanomi et al, 2020). The soil is poorly developed and dominated by calcareous soils.…”
Section: Study Sitesmentioning
confidence: 99%